2004
DOI: 10.1111/j.1365-2621.2004.00777.x
|View full text |Cite
|
Sign up to set email alerts
|

Fish scale collagen. Preparation and partial characterization

Abstract: Fish scale was decalcified and disaggregated and then collagen was prepared by limited pepsin digestion. The yields of collagens were very high on a dry weight basis; sardine 50.9%, red sea bream 37.5% and Japanese sea bass 41.0%, respectively. These scale collagens were heterotrimers with a chain composition of (a1) 2 a2. Although the denaturation temperature of the collagen was lower than land animal collagen, fish scales will have potential as an important collagen source for use in various industries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
94
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(110 citation statements)
references
References 16 publications
9
94
0
4
Order By: Relevance
“…The amino acid contents of both fish types vary among the three tissues selected (skin, scales, and fins). Similar results have been reported by Nagai et al (2004), who observed that the collagen amino acid contents correlated with the water temperature of their normal habitat. Methionine and cysteine were negligible in the C. catla and C. mrigala skin, scales, and fins from the three weight groups.…”
Section: Amino Acid Analysissupporting
confidence: 79%
See 1 more Smart Citation
“…The amino acid contents of both fish types vary among the three tissues selected (skin, scales, and fins). Similar results have been reported by Nagai et al (2004), who observed that the collagen amino acid contents correlated with the water temperature of their normal habitat. Methionine and cysteine were negligible in the C. catla and C. mrigala skin, scales, and fins from the three weight groups.…”
Section: Amino Acid Analysissupporting
confidence: 79%
“…2). Nagai and Suzuki (2000); Nagai et al (2004); Rodziewicz-Motowidlo et al (2008) and Nagai et al (2008) reported that collagen is the primary protein in preparing 75 % of the protein contents. The remaining 25 % is composed of smaller fragments that appear under the α bands corresponding to the molecular weight ranging from 73 to 155 kDa, including the probable elastin bands (8 %) and the remaining unidentified proteins and peptides (17 %).…”
Section: Resultsmentioning
confidence: 99%
“…The amino acid composition of gelatin from tilapia scales is also determined and given in Table 1. The glycine content was most abundant, which was similar to that of gelatins from sardine, red sea bream and Japanese sea bass scales (Nagai et al 2004). The imino acid (proline and hydroxyproline) content of tilapia scale gelatin was 212 residues per 1,000 amino acid residues, which was similar to that of warm-water fish gelatins (Nagai et al 2004;Avena-Bustillos et al 2006) and higher than that of tilapia skin gelatin (Weng et al 2013).…”
Section: Resultsmentioning
confidence: 59%
“…The marine collagens showed high solubility at acidic pH (4 to 5) and the solubility markedly decreased in the presence of NaCl up to 2%. Type I collagen has also been extracted from skin, bone, fins, and scales of fresh water and marine fishes, chicken skin and different marine animals such as squid, octopus, jellyfish, starfish and fish (Swatschek et al, 2002;Sadowska et al, 2003;Nagai et al, 2004;Falguni et al, 2010). Collagens from these sources were evaluated for their potential applications as alternatives to mammalian collagen.…”
Section: Solubility Of Collagensmentioning
confidence: 99%